2011
DOI: 10.1111/j.1753-4887.2011.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on adiponectin levels in blood

Abstract: Dietary management has been considered an alternative means of modulating adiponectin levels. The purpose of this review is to examine the scientific evidence regarding the effect of diet on adiponectin levels in blood. Clinical trials were selected from Medline until April 2010 using the following MeSH terms: adipokines OR adiponectin AND diet OR lifestyle. A total of 220 articles were identified in the initial search, and 52 studies utilizing three different methods of dietary management were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 76 publications
(529 reference statements)
7
68
1
2
Order By: Relevance
“…The modest effect of weight change on plasma total adiponectin observed in this study is also consistent with the literature. A recent review found that consistently, significant increases in plasma adiponectin require substantial weight loss of ~7% [24]. While we observed a trend for a time × weight change interaction, confirming that body weight is an important factor in determining plasma adiponectin concentrations, the effect size was very modest, again likely related to the more modest average weight loss in this study compared to previous longer-term studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The modest effect of weight change on plasma total adiponectin observed in this study is also consistent with the literature. A recent review found that consistently, significant increases in plasma adiponectin require substantial weight loss of ~7% [24]. While we observed a trend for a time × weight change interaction, confirming that body weight is an important factor in determining plasma adiponectin concentrations, the effect size was very modest, again likely related to the more modest average weight loss in this study compared to previous longer-term studies.…”
Section: Discussionsupporting
confidence: 65%
“…It has therefore remained unclear whether the effects of their dietary intervention may be due to hidden time effects. A recent review therefore concluded that data on the effect of macronutrient composition on plasma adiponectin concentrations are largely inconclusive [24]. The data for measures of low-grade systemic inflammation such as CRP are similarly inconclusive, again largely due to the difficulty in disentangling the relative effects of changes in macronutrient composition and energy balance on the concentrations of the plasma biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…For adiponectin, most weight loss trials including the SHAPE-2 do not observe significant improvements. Reviews suggest that at least 7.5% to 10% weight loss is needed to induce effects (40,47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased adiponectin levels were already apparent after 1 week (two to three bouts) of moderately intense aerobic exercise, in some cases up to 260% [99]. Regarding diet modifications, several studies reported that daily intake of fish or omega-3 supplementation increased adiponectin levels by amounts ranging from 14 to 60% [100]. Furthermore, adherence to a Mediterranean dietary pattern showed excellent results in T2DM women [101].…”
Section: Introductionmentioning
confidence: 99%